Crystalline Quality of CdSe Single Crystalline Commercial Wafer - Núñez García, Javier Luis Mariano (2015)
Cadmium selenide is II-VI semiconductor compound with 1.67 eV energy gap (≈ 300 K) and high stopping power for nuclear radiation. Its crystalline structure is hexagonal (wurtzite) and it is used in solar cells, transistors, light emitting diodes, electroluminescent devices, nuclear radiation detectors at room temperature and nonlinear optical devices. It is also employed as substrate for epitaxial growth of HgCdSe. Qualities of devices are critically dependent on their material properties. Crystalline characterization of a CdSe commercial wafer was our main goal. The crystalline quality was evaluated by different techniques. Since it is used as an optical window in the IR spectrum, its optical transmittance was measured by FTIR. The etch pits distribution was determined by chemical etching. Dislocation density was obtained by counting on optical micrographs meanwhile misorientation between adjacent subgrains by means of Shockley - Read approximation. The reliability of the techniques used in determining the crystalline quality was evaluated. The etching solution was sensitive in linear defects detection and crystalline quality was adequate for devices manufacture of this material. Transmission electron microscopy employment confirmed these result.